Gentrification and touristification in Costa Rica: perceptions of the impacts of “expats” resident in Guanacaste - Hernández Murillo, Jason (2025)
This article analyzes the perceptions of the Costa Rican population regarding the impact of expatriate residents on the processes of gentrification and touristification in the province of Guanacaste, Costa Rica. To this end, a quantitative methodology was employed, based on secondary data analysis from a survey conducted by the Instituto de Estudios Sociales en Población of the Universidad Nacional (IDESPO-UNA) between July and August 2024. The main results indicate that most respondents acknowledge the presence of expatriates in the region, with a high concentration in Guanacaste. Furthermore, expatriates are perceived as contributing to the increase in property values and the overall cost of living. Finally, there is a significant public demand for the implementation of regulations aimed at mitigating these socioeconomic effects.